Risk of severe and opportunistic infections and the impact of SARS‐COV‐2 on this risk in a nationwide cohort of patients with inflammatory bowel disease. Issue 7 (16th January 2023) - Khan, Nabeel; Mahmud, Nadim; Patel, Manthankumar; Sundararajan, Ramaswamy; Reinisch, Walter
Summary: Background: The Inflammatory Bowel Disease (IBD) patients have adopted lifestyle modifications to prevent infection via SARS COV‐2. Aims: This study aims to examine rate of serious infections and opportunistic infections in the pre‐pandemic and pandemic period, and to analyse if the risk associated with medications used to treat IBD were potentially modified by associated change in lifestyle. Methods: We conducted a retrospective cohort study of patients from the US national Veteran Affairs Healthcare System (VAHS). Patients were stratified into two groups: pre‐pandemic (prior to SARS COV‐2 pandemic) and pandemic (during SARS COV‐2 pandemic) and outcomes were measured in these groups. Primary outcome was occurrence of any serious infection. Secondary outcome was occurrence of any opportunistic infection. Results: There were 17, 202 IBD patients in the pre‐pandemic era and 15, 903 patients in the pandemic era. The pre‐pandemic era had a significantly higher proportion of serious infections relative to the pandemic era (5.1% vs. 4.4%, p  = 0.002). The proportion of opportunistic infections were similar between pre‐pandemic and pandemic eras (0.3% vs. 0.3%, p  = 0.82). Relative to 5‐ASA, patients taking anti‐TNF (HR = 1.50 (1.31–1.72)), anti‐TNF+TP (HR = 1.56 (1.24–1.95)) or vedolizumab (HR = 1.81 (1.49–2.20)) had an increased hazard of serious infection ( p  > 0.001). Conclusion: In a nationwide cohort of IBD patients, we found that risk of serious infections could possibly be affected by behavioural modifications due to SARS‐COV‐2 pandemic. Abstract : There was fall in serious infections among IBD patients during the pandemic and the fall was most notable among patients on combination of thiopurines and anti‐TNF agents relative to patients on 5‐ASA.